2021
DOI: 10.3390/educsci11050231
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of a Synchronous Online Cooperative Learning Course in a Japanese Women’s University during the COVID-19 Pandemic

Abstract: As the coronavirus disease 2019 (COVID-19) pandemic expanded worldwide, most Japanese universities launched online learning as an emergent measure; hence, securing the quality of online learning remains a challenge. This study aimed to understand reasons behind students’ preferred mode of online learning during the pandemic and to explore the impact of online cooperative learning on students’ class participation by analyzing their voluntary comments. A qualitative content analysis identified three factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 41 publications
2
19
0
6
Order By: Relevance
“…Several case studies were conducted [18][19][20] but these, too, focused on specific departments or modules within a university. Both qualitative [21,22] and quantitative research [8,[23][24][25][26] was conducted, both in developing [27][28][29][30], and developed countries [31][32][33] as well as in post-communist countries [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Several case studies were conducted [18][19][20] but these, too, focused on specific departments or modules within a university. Both qualitative [21,22] and quantitative research [8,[23][24][25][26] was conducted, both in developing [27][28][29][30], and developed countries [31][32][33] as well as in post-communist countries [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of active learning refers to activities that induce students in a thinking process about the new information and connect it with experience or knowledge [42,44]. There is a great variety of activities that can be considered as active learning, such as discussion in small groups, peer activities, individual activities that required a mental effort, interactions, study cases, problem resolution, laboratories, quizzes, and games, all of them have to guarantee that students think effectively [42][43][44][45][46]. The advantages include that students feel more secure sharing their ideas in small groups, developing critical thinking, retaining new knowledge, developing communication and leadership skills, and feeling more motivated and interested [42,[44][45][46][47].…”
Section: Usa Xmentioning
confidence: 99%
“…The great benefit of synchronous learning is that it makes students feel connected with their instructors and peers due to face communications presented in instruction. Students can have an active discussion, cooperation, immediate feedback, personal contact with the instructor and classmates and individual guidance (Sugino, 2021). For EFL learning, Ozdal et al (2021) found that although online language learning was not as effective as in-person learning, students preferred synchronous learning to asynchronous courses because they offer a similar experience as face-to-face learning.…”
Section: Conceptual Framework 1synchronous Learningmentioning
confidence: 99%